PENGARUH LINGKUNGAN SEKOLAH TERHADAP RESILIENSI SISWA DALAM MENGATASI TOXIC FRIENDSHIP DI SMA SWASTA NASRANI 2 MEDAN - Gladis Rebeka Sinaga; Sanggam Pardede; Elisabeth Margareta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of the school environment on students' resilience in dealing with toxic friendship, with toxic friendship acting as a mediating variable at SMA Swasta Nasrani 2 Medan. This research employed an explanatory quantitative approach using a total sampling technique involving 70 students as respondents. Data were collected through a Likert-scale questionnaire and analyzed using linear regression, partial test, and Sobel test with the assistance of SPSS Version 26. The results indicate that the school environment has a positive and significant effect on students' resilience, with a t-value of 6.303 and a significance level of 0.000. In addition, the school environment also has a positive and significant effect on toxic friendship, with a t-value of 19.868 and a significance level of less than 0.001. Furthermore, toxic friendship shows a positive and significant effect on students' resilience, with a t-value of 4.434 and a significance level of less than 0.001. Moreover, the mediation test reveals that toxic friendship significantly mediates the relationship between the school environment and students' resilience, as indicated by a t-value of 3.202 and a significance level of 0.001. These findings suggest that a conducive school environment contributes to enhancing students' resilience, both directly and indirectly through the formation of healthier peer relationships. Therefore, it is essential for schools to create a supportive environment in order to strengthen students' mental resilience.